Portable 3D-printed hand orthosis with spatial stiffness distribution personalized for assisting grasping in daily living - Park, Chan Beom; Park, Hyung-Soon (Frontiers in Bioengineering and Biotechnology, 2023)
Stroke survivors having limited finger coordination require an active hand orthosis to assist them with grasping tasks for daily activities. The orthosis should be portable for constant use; however, portability imposes constraints on the number, size, and weight of the actuators, which increase the difficulty of the design process. Therefore, a tradeoff exists between portability and the assistive force. In this study, a customizable and highly portable hand orthosis was designed to assist with grasping tasks as per user intentions. The designed orthosis weighs 454 g and includes a single tiny motor for twisted string actuation and a 3D-printed passive elastic structure based on 3D scans of the hand to aid with bidirectional finger movement. Because the required assistive force depends on individual joint characteristics, the stiffness of the structure is optimized based on measurements of individual hand parameters to achieve a sufficient grip aperture in the pre-grasping phase and minimal assistive force in the grasping phase. Ten stroke survivors were recruited to evaluate the system. Sufficient grip aperture and grip strength were achieved, confirming that the variable stiffness design of the structure can effectively replace actuators for assistance. The orthosis also significantly restored the range of motion and improved the performance of daily activities. The personalized orthosis can assist with grasping in daily living. The user-specific design considering individual joint characteristics is a promising approach for improving the portability of active orthoses with reduced number, size, and weight of actuators for assistance.